Bhagavan Ramana: the extravagant boon giver - Natarajan, Arni R. (Ramana Maharshi Centre for Learning, 2006)
Contributed articles on the miracles and boons of Ramana Maharshi, 1879-1950, Hindu philosopher and saint from Tamil Nadu, India